How do host plant use and seasonal life cycle relate to insect body size: A case study on European geometrid moths (Lepidoptera: Geometridae). (23rd March 2023) - Seifert, Carlo L.; Strutzenberger, Patrick; Fiedler, Konrad
Abstract: We used European geometrid moths (>630 species) as a model group to investigate how life history traits linked to larval host plant use (i.e., diet breadth and host‐plant growth form) and seasonal life cycle (i.e., voltinism, overwintering stage and caterpillar phenology) are related to adult body size in holometabolous insect herbivores. To do so, we applied phylogenetic comparative methods to account for shared evolutionary history among herbivore species. We further categorized larval diet breadth based on the phylogenetic structure of utilized host plant genera. Our results indicate that species associated with woody plants are, on average, larger than herb feeders and increase in size with increasing diet breadth. Obligatorily univoltine species are larger than multivoltine species, and attain larger sizes when their larvae occur exclusively in the early season. Furthermore, the adult body size is significantly smaller in species that overwinter in the pupal stage compared to those that overwinter as eggs or caterpillars. In summary, our results indicate that the ecological niche of holometabolous insect herbivores is strongly interrelated with body size at maturity. Abstract : We used European geometrid moths (Lepidoptera) to study how larval host plant use and seasonal life cycle relate to adult body size in holometabolous insect herbivores. We found that species associated with woody plants are, on average, larger than herb feeders and increase in size with increasing diet breadth. Obligatorily univoltine species are larger than multivoltine species, and attain larger sizes when their larvae occur exclusively in the early season. We further found that adult body size is significantly smaller in species that overwinter in the pupal stage compared to taxa overwintering as eggs or caterpillars. These results suggest that the ecological niche of holometabolous insect herbivores is strongly interrelated with body size at maturity.